Evaluating short-term and survival outcomes of natural orifice specimen extraction surgery for colorectal cancer: A single-centre retrospective study - Zhao, Fuqiang; Zhao, Wei; Xiao, Tixian; Wang, Zhijie; Huang, Fei; Xing, Wei; Liu, Qian (Frontiers in Surgery, 2023)
Background Natural orifice specimen extraction surgery (NOSES) has been confirmed as an alternative approach without auxiliary incisions. The purpose of this study was to investigate the short-term and survival outcomes of NOSES versus conventional laparoscopic surgery (LAP) in treatment of sigmoid and high rectal cancer. Method The retrospective study was conducted at single centers between January 2017 to December 2021. Relevant data included clinical demographics, pathological features, operative parameters, postoperative complications and survival outcomes were collected and analyzed. All procedures were performed using either a NOSES or a conventional LAP approach. Propensity score matching (PSM) was conducted to balance clinical and pathological features between the two groups. Results After PSM, a total of 288 patients were eventually included in this study, 144 in each group. Patients in the NOSES group experienced faster recovery of gastrointestinal function (2.6±0.8 vs. 3.6±0.9 d, P=0.037), less pain and less analgesia required (12.5% vs. 33.3%, P<0.001). In addition, the incidence of surgical site infection in the LAP group was significantly higher than that in the NOSES group (12.5% vs 4.2%, P=0.011), especially incision-related complications (8.3% vs 2.1%, P=0.017). After a median follow-up of 32 (range, 3–75) months, the two groups had similar 3-year overall survival rates (88.4% vs. 88.6%; P = 0.850) and disease-free survival rates (82.9% vs. 77.2%; P = 0.494). Conclusion The transrectal NOSES procedure is a well-established strategy with advantages in reducing postoperative pain, faster recovery of gastrointestinal function, and less incision-related complications. In addition, the long-term survival is similar between NOSES and conventional laparoscopic surgery.